Nigeria -U.S cooperation on counterinsurgency: a critical examination of the structures and dimensions of U.S technical aid to Nigeria - D.C, Ndidigwe (SPC Journal of Social Sciences, 2020)
Terrorism and measures to countering it has been a major challenge to the country worst hit by the menace. The attention of the international community has focused on countering extremism in the North-East region of Nigeria ever since. This paper evaluates the Nigeria- US cooperation on counterinsurgency with emphasis on the structures and dimensions of the latterâ€™s technical aid to the former. The paper also highlights the importance of collaboration and cooperation with other countries to contain insurgency, albeit concerted efforts from both parties. However, the paper was apt to point that technical aid of whatever variant is insufficient and barely enough to decimate insurgency as such, more often than not progress in such cooperative relations is always at the whims and caprices of the donor or giver nation. It recommends that, a countryâ€™s pursuit of a robust counterterrorism strategy must have some local panache interlaced with external input.Â Â